Antiglobulin consumption test with sera from patients with myasthenia gravis - Aarli, J. A. (1970)
The antiglobulin consumption test was performed with sera from patients with myasthenia gravis, lyophilized skeletal muscle tissue serving as antigen. Incubation of the saline-treated tissue preparation with the antiglobulin serum resulted in a small titre reduction of antiglobulin, indicating in vivo binding of γ-globulins to the tissue (basal consumption). Treatment of the tissue with normal human serum resulted in a greater consumption. This was mediated by γG-globulins, normally present in human sera and with the capacity of binding to skeletal muscle (normal consumption). Sera from twenty-four patients with myasthenia gravis were tested in the antiglobulin consumption test. A positive reaction (pathological consumption) was observed in twelve (50%). Cross-reactions with cardiac muscle and thymus were demonstrated.